Electron Behavior in Beam Diode Driven by Intense Pulsed Power Device for Warm Dense Matter State Research of Inertial Confinement Fusion. (December 2017) - Shahed-Uz-Zaman, Md.; Takahashi, Kazumasa; Sasaki, Toru; Kikuchi, Takashi; Harada, Nob.
Abstract: Electron behavior in beam diode gap was analyzed numerically based on the normalized value of intense pulsed power discharge device ETIGO-II as impedance controller for dense matter state research of inertial confinement fusion. After emission of electrons from the cathode surface, acceleration time, impedance, potential distribution and velocity varies with the function of different beam diode gap. To understand the time dependent behavior of electron and beam output current for different beam diode gap, 2-d electrostatic particle-in-cell (PIC) model was carried out. According to the numerical analysis, it was found that beam output current decreases with the increase of beam diode gap distance. The electron beam diode impedance was also observed increasing with the increase of diode gap. Numerical result reproduced experimental data and useful for the understanding of experimental result for dense matter state research of inertial confinement fusion.